Bumdes Acceleration Towards Mandiri Village - Khairul Amri (Indonesian Association for Public Administration (IAPA), 2019)
Village-owned enterprises (BUMDES) are village business institutions that are managed by the community and village government in an effort to strengthen the village economy and be formed based on the needs and potential of the village. In fact there are some villages that have succeeded in running and developing BUMDes, but there are still many BUMDES that are stagnant and even unproductive in Indonesia. The purpose of this study is to determine the conditions and governance of BUMDes that are successful and growing. The method used is a qualitative approach, this type of research uses literature studies by looking for theoretical references relevant to the case or problem found. The results of this study indicate that the Empowerment of Village Communities by the government through the Village Owned Enterprises (BUMDes) program is an appropriate and relevant effort to Indonesia which is geographically very broad and has diverse potential in each region and village. BUMDes can be the main wheel of economic drivers in the village. But, the acceleration is still not optimal, if seen from the number of BUMDes that succeed with the Number of Villages in Indonesia, it needs to be a common concern in order to improve and achieve goals